DEVELOPMENT OF MEASURES TO ASSESS AND MANAGE THE MORPHOLOGICAL COMPOSITION OF HOUSEHOLD WASTE IN EDUCATIONAL INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The reliability of the scientific statements and the results of the conducted research is confirmed by the use of modern methods of theoretical and experimental research, comparison of the results obtained with the results of other authors' work in close areas of research, sufficient convergence of model and experimental data (during verification, the relative error of the calculated data was 0.6-7%), positive experience in the practical implementation of research results.